2012
DOI: 10.1126/scitranslmed.3004145
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Paralysis and Reduced Inflammation from Peripheral Administration of β-Amyloid in T H 1 and T H 17 Versions of Experimental Autoimmune Encephalomyelitis

Abstract: Abstractβ-amyloid-42 (Aβ42) and β-amyloid-40 (Aβ40), major components of senile plaque deposits in Alzheimer's disease (AD), are considered neurotoxic and pro-inflammatory. In multiple sclerosis (MS), Aβ42 is upregulated in brain lesions and damaged axons. Here we found, unexpectedly, that treatment with either Aβ42 or Aβ40 peptides reduced motor paralysis and brain inflammation in four different models of experimental autoimmune encephalomyelitis (EAE) with attenuation of motor paralysis, reduction of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 63 publications
4
78
0
1
Order By: Relevance
“…That amyloid forming peptides are immunosuppressive and therapeutic is counterintuitive to the manifold publications emphasizing their correlation with inflammation. However, we have observed similar effects when ␤ amyloid peptides are used as treatment for EAE (48) and currently are exploring the molecular basis for these effects.…”
Section: Tablementioning
confidence: 66%
“…That amyloid forming peptides are immunosuppressive and therapeutic is counterintuitive to the manifold publications emphasizing their correlation with inflammation. However, we have observed similar effects when ␤ amyloid peptides are used as treatment for EAE (48) and currently are exploring the molecular basis for these effects.…”
Section: Tablementioning
confidence: 66%
“…Moreover, Eisenberg and colleagues had shown that there was a minimal hexapeptide motif in these proteins that had sufficient energy to form β zipper structures and amyloid fibrils (84,85). An entrepreneurial PhD student, Jacqueline Grant, had shown that injection of β-amyloid peptides 1-40 or 1-42, thought to be pathogenic in Alzheimer's disease, were capable of suppressing EAE (86 (104,105). Proinsulin is at the top of the list of antigens that are targets of the autoimmune response in type 1 diabetes (104,105).…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…Given the association of amyloid proteins with neurodegenerative diseases, Steinman expected that administering amyloid proteins in the EAE model would exacerbate the inflammation. Instead, mice receiving an intravenous infusion of amyloid "started walking around" (13). Steinman was as surprised as anyone else, but he now sees a different role for amyloid proteins in MS. "If you look under the microscope at diseases like Alzheimer's or Parkinson's, you don't see much evidence of an inflammatory response.…”
Section: Fresh Perspective On Amyloidmentioning
confidence: 99%